The Historical and Lived Sources of Collective Memory - Muller, Felipe (2013)
The aim of the present paper is to study the role that lived and historical memories havein the conformation of collective memory through the participant’s appraisals in the recent past of Argentina. These memories operate as sources that nurture collective memory. Lived memories are related to live experiences, while historical memories are related to indirect sources that inform about the past. 60 participants, divided in two groups (above and below 46 years of age) appraised the present and recent past, based on lived and historical memories. Results show that lived or autobiographical and historical memories contribute differently to collective memory.